2017
DOI: 10.1177/0969733017724611
|View full text |Cite
|
Sign up to set email alerts
|

Nurses performance in clinical ethics committees and commissions: An integrative review

Abstract: This was an integrative review of articles published in national and international journals between 1994 and 2016 which described the participation of nursing professionals in ethics commissions. Participants and research context: A total of 35 articles were selected. Discussion and conclusion for this article: The thematic categories were the need for time to discuss ethical issues; ethics committee to reduce the moral suffering of professionals; competencies required for participation; and barriers/difficult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…(a) the personal and professional attributes of CEC members [7,16,79,[81][82][83][84][85][86] and the composition, training, experience [70,[78][79][80] and skillset of the team [69, 78-81, 83, 86-96] carrying out the CECons (92-94); (b) the approach adopted and if it considered the ethical, legal, moral, financial, clinical and professional issues holistically and objectively, and whether the process considered prevailing sociocultural and practical issues [5,14,73,88,[99][100][101]105] in a confidential manner [15,79,90,103,108]. Also considered was if the CECons was timely [31,79,109,110], well-documented, structured, accessible [5,9,31], clearly communicated [5,77,79,91,92,99,[111][112][113][114][115][116]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(a) the personal and professional attributes of CEC members [7,16,79,[81][82][83][84][85][86] and the composition, training, experience [70,[78][79][80] and skillset of the team [69, 78-81, 83, 86-96] carrying out the CECons (92-94); (b) the approach adopted and if it considered the ethical, legal, moral, financial, clinical and professional issues holistically and objectively, and whether the process considered prevailing sociocultural and practical issues [5,14,73,88,[99][100][101]105] in a confidential manner [15,79,90,103,108]. Also considered was if the CECons was timely [31,79,109,110], well-documented, structured, accessible [5,9,31], clearly communicated [5,77,79,91,92,99,[111][112][113][114][115][116]…”
Section: Discussionmentioning
confidence: 99%
“…The primary reason for evaluating CECons was to certify [67][68][69] or accredit [9] CEC consultants to ensure that they possessed the 'necessary competencies' [70]. CECons were also assessed to determine their impact on patient care [18,[71][72][73][74][75] and benchmark their programs against prevailing standards [17,76,77].…”
Section: Purpose Of Cecon Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that nursing professionals recognize the importance of commissions, and for such insertion, specific knowledge, skills, and attitudes are required to work in the area. Greater contact between NECs and professionals through educational activities can contribute to greater bonding between professionals, service, and regulatory bodies (20) . Currently, the state of Goiás has 62 NECs, which shows the strengthening of these instances as representatives of the Council.…”
Section: Ethics In Nursing: Categorization Of Legal Processesmentioning
confidence: 99%
“…Thus, the high frequency of ethical infractions observed in this study reflects the low adherence of professionals to NCPE, which suggests a deficit in the knowledge of ethical-legal aspects of the profession (25) . Therefore, to reduce the gap between professional practice and compliance with nursing regulations, there is a need to implement strategies such as the implementation of NECs (20) and the development of ethical competences during the training period (26) .…”
Section: Study Limitationsmentioning
confidence: 99%